Karakter Agronomi dan Hasil Galur Padi Toleran Rendaman - Hairmansis, Aris; Supartopo, Supartopo; Kustianto, Bambang; Pane, Hamdan (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Use of submergence tolerant rice (Oryza sativa L.) cultivar for planting is an important adaptation strategy to reduce yield losses in flood prone rice areas. The aim of this study was to investigate the agronomic characteristics of submergence tolerant rice lines in a controlled environment. Six submergence tolerant rice lines carrying gene Sub1 and their respective susceptible parents were evaluated. Rice cultivars Inpara 3 (tolerance) and IR42 (susceptible) were used as control. All rice genotypes were grown in replicated plots under two different environments, i.e., normal irrigation and 10 days complete submergence at vegetative plant stage. Results showed significant variations among rice genotypes for agronomic characteristics under the two different environments. Under the submergence condition, tolerant rice lines produced higher yields than did their parents, while under normal irrigation they performed comparably to their parents. Three tolerant lines, i.e., BR11-Sub1, Swarna-Sub1, and TDK1-Sub1 produced 5.76, 5.74, and 5.68 t/ha grain yield, respectively, under complete submergence for 10 days. These lines were considered as tolerant to submergence, and need to be tested further in a multi-location yield trial, in the targeted environments.